DIDACTIC MECHANISM FOR DEVELOPING PIANO TEACHING IN HIGHER EDUCATION INSTITUTIONS - Normuminova Gulmira Komiljonovna (Modern American Journals, 2025)
In higher education institutions, piano subjects are especially widely manifested in the mastering of the didactic mechanism of performing and teaching works on the instrument by future music teachers, the expansion of the instrumental creativity of future music teachers, the free interpretation of form features, the diversity of the style of expression on solo instruments, the subtle use of the proportion of timbres, and the careful use of harmonic and technical capabilities. The works studied in piano subjects in higher education acquire the color of beautiful sounds and the rich harmonic harmony that has developed in historical stages.
Keywords: Timbre color, dynamic resonance, didactics, etude, technique, polyphony, instrument, tempo, color, stroke.